Analisis Konten Materi Fikih Berbasis Prinsip Muhkam dan Amm Khas dalam Kurikulum Madrasah Aliyah: Penelitian - Nailus Sha’adah; Ahmad Hanif Fahruddin (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Education is an important component for the progress and success of a nation. In Madrasah Aliyah, there are subjects about Islamic law contained in Fiqh. Unintentionally, studying Fiqh in the Madrasah Aliyah curriculum is also similar to learning about Muhkam and Amm Khas. In this article, the researcher will explain a brief understanding of Muhkam and Amm Khas, examples of Fiqh materials that are considered Muhkam and Amm Khas, as well as their pedagogical implications for institutions, teachers, and students. Using a qualitative research method of the Library Research type, the findings include Fiqh teaching materials that are part of Muhkam and Amm Khas. With the elaboration of Muhkam and Amm Khas in the teaching materials, it is expected that teachers also read other literature so that when delivering the material, they are not limited to a single viewpoint. This effort becomes a commitment for Fiqh teachers to continuously think about various perspectives, so that students will adopt the teacher's way of thinking in their daily lives, enabling them to examine the basis of other people's acts of worship and not easily criticize the legal foundations of others.